Introduction to bioinformatics : (Humana Press, 2003)
The genomic revolution that has spawned microarrays and high throughput technologies has produced vast amounts of complex biological data that require integration and multidimensional analysis. In Introduction to Bioinformatics: A Theoretical and Practical Approach, leading researchers and experts introduce the key biological, mathematical, statistical, and computer concepts and tools necessary for physical and life scientists to understand and analyze these data. For physical and computer scientists, the book provides a sound biological framework for understanding the questions a life scientist would ask in the context of currently available computational tools. Here, the basic cellular structure and the biological decoding of the genome, the long-range regulation of the genome, the in silico detection of the elements that impact long-range control, and the molecular genetic basis of disease as a consequence of replication are explained. Reviews of clinical human genetics, the various clinical databases, and pertinent issues in population genetics complete this tutorial.